Climate change VR - Tan, Kenrick Yong Heng (Nanyang Technological University, 2021)
The increased integration of Virtual Reality (VR) into the current society, allows the user to have a surreal experience in a virtual world in a safe environment. The effects of climate change have been witnessed for several decades now and it appears to be getting worse. While this technology is integrated into many sectors, we could use it to educate the youth about climate change. This project is tasked with the creation of an interactive 3D climate change VR game that shows various effects of climate changes and being able to see the changes take place. This report discusses the effectiveness of various existing VR games in trying to educate the public on climate change, and how we could incorporate the element of player interactivity into a new climate change VR game to engage the player. This project brings the player on a journey to gather clues from an old historic journal of what happened on Earth and through traveling to 3 different locations on Earth. Ultimately, coming to the conclusion that the cause was drastic climate changes.